Assessment of physiological races of Exserohilum turcicum isolates from maize in Argentina and Brazil - Navarro, Barbara Ludwig (2021)
Northern corn leaf blight (NCLB) is one of the most important diseases in maize worldwide. It is caused by the fungus Exserohilum turcicum, which exhibits a high genetic variability for virulence, and hence physiological races have been reported. Disease control is based mainly on fungicide application and host resistance. Qualitative resistance has been widely used to control NCLB through the deployment of Ht genes. Known pathogen races are designated according to their virulence to the corresponding Ht gene. Knowledge about of E. turcicum race distribution in maize-producing areas is essential to develop and exploit resistant genotypes. Maize leaves showing distinct elliptical grey-green lesions were collected from maize-producing areas of Argentina and Brazil, and 184 monosporic E. turcicum isolates were obtained. A total of 66 isolates were collected from Argentina during 2015, 2018 and 2019, while 118 isolates from Brazil were collected during 2017, 2018 and 2019. All isolates were screened on maize differential lines containing Ht1, Ht2, Ht3 and Htn1 resistance genes. In greenhouse experiments, inoculated maize plants were evaluated at 14 days after inoculation. Resistance reaction was characterized by chlorosis, and susceptibility was defined by necrosis in the absence of chlorosis. The most frequent race was 0 in both Argentina (83%) and Brazil (65%). Frequencies of race 1 (6% and 24%) and race 23N (5% and 10%) were very low in Argentina and Brazil, respectively. The high frequency of race 0 isolates provides evidence that qualitative resistance based on the tested Ht genes is not being used extensively in Argentina and Brazil to control NCLB. This information may be relevant for growers and breeding programs as the incidence of NCLB is increasing in both countries.